Altered sensorimotor processing in irritable bowel syndrome: Evidence for a transdiagnostic pathomechanism in functional somatic disorders - Schröder, Lena; Regnath, Franziska; Glasauer, Stefan; Hackenberg, Anna; Hente, Juliane; Weilenmann, Sonja; Pohl, Daniel; von Känel, Roland; Lehnen, Nadine (Frontiers in Neuroscience, 2022)
Objective A recent hypothesis suggests that functional somatic symptoms are due to altered information processing in the brain, with rigid expectations biasing sensorimotor signal processing. First experimental results confirmed such altered processing within the affected symptom modality, e.g., deficient eye-head coordination in patients with functional dizziness. Studies in patients with functional somatic symptoms looking at general, trans-symptomatic processing deficits are sparse. Here, we investigate sensorimotor processing during eye-head gaze shifts in irritable bowel syndrome (IBS) to test whether processing deficits exist across symptom modalities. Methods Study participants were seven patients suffering from IBS and seven age- and gender-matched healthy controls who performed large gaze shifts toward visual targets. Participants performed combined eye-head gaze shifts in the natural condition and with experimentally increased head moment of inertia. Head oscillations as a marker for sensorimotor processing deficits were assessed. Bayes statistics was used to assess evidence for the presence or absence of processing differences between IBS patients and healthy controls. Results With the head moment of inertia increased, IBS patients displayed more pronounced head oscillations than healthy controls (Bayes Factor 10 = 56.4, corresponding to strong evidence). Conclusion Patients with IBS show sensorimotor processing deficits, reflected by increased head oscillations during large gaze shifts to visual targets. In particular, patients with IBS have difficulties to adapt to the context of altered head moment of inertia. Our results suggest general transdiagnostic processing deficits in functional somatic disorders.